2018
DOI: 10.1002/jbio.201800085
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of intracellular oxygen and cell metabolism by simultaneous PLIM of phosphorescent TLD1433 and FLIM of NAD(P)H

Abstract: During photodynamic therapy (PDT), disruption of cell respiration and metabolic changes could be one of the first events. Photophysical characteristics of the photosensitizer (PS) and its specific redox potential define consumption of molecular oxygen followed by generation of reactive oxygen species. The potential PS TLD1433 is based on transition metal Ru(II) and possess an oxygen-dependent luminescence. This enables the study of oxygen consumption by PS-phosphorescence lifetime imaging (PLIM) and simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…The emission spectrum of TLD1433 under two-photon excitation was measured in solution as well as within living cells and presented previously. 4,25 Similar to other ruthenium (II) complexes investigated by us, the tris-(2,2 0 -bipyridyl) dichloride (Ru (bpy) 2þ 3 ) and cHSA-PEO-TPP-Ru, TLD1433 emits in the range from 550 nm and 670 nm. 20,26 We were able to perform two-photon microscopy using the 250 MHz Ti:Sa on a Zeiss LSM 710 NLO.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The emission spectrum of TLD1433 under two-photon excitation was measured in solution as well as within living cells and presented previously. 4,25 Similar to other ruthenium (II) complexes investigated by us, the tris-(2,2 0 -bipyridyl) dichloride (Ru (bpy) 2þ 3 ) and cHSA-PEO-TPP-Ru, TLD1433 emits in the range from 550 nm and 670 nm. 20,26 We were able to perform two-photon microscopy using the 250 MHz Ti:Sa on a Zeiss LSM 710 NLO.…”
Section: Resultssupporting
confidence: 53%
“…3 Within this study, investigations where done with a 250 MHz repetition rate laser and compared with 80 MHz excitation. As will be discussed within this paper, PLIM imaging could be very well achieved at 250 MHz excitation rate, however, simultaneous FLIM¯tting procedures, recently published with 80 MHz excitation rate, 4 need further modi¯cations in the detection electronics (see Sec. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this PS is still being elucidated, but a recent study indicated that the complex may localize in the endosomal or lysosomal organelles. 95 Ruthenium(II) complexes can undergo receptor-mediated transport into cells by association with transferrin; hence, in a study, complex 99 was premixed with transferrin to allow for the formation of Rutherrin before administration into AY27 cells and subcutaneous CT26.CL25 tumor mice models. 96 Rutherrin was found to improve cellular uptake and maintain the structural integrity to produce an increase in the defining PDT effect of complex 99.…”
Section: ■ Therapeutic Luminescent Complexesmentioning
confidence: 99%
“…Cell localisation of TLD-1433 and its impact on cell metabolism by changing the cellular redox balance was published in a recent study. 24 Cyclometalated Ru(II) complexes are usually more photostable and their absorption spectra is red-shifted compared to diamine Ru(II) complexes. The (photo-)toxicity of the complexes was checked in two cell lines, namely SK-MEL-28 (melanoma) and CCD-1064Sk (normal skin fibroblasts).…”
Section: Figure 2 Tld-1411 and Tld-1433mentioning
confidence: 99%